Pengaruh Senam Kreasi terhadap Perkembangan Emosional Anak Usia Dini Kelompok A - Neng Awalia Farida; Risna Nurul Insani; Aeni Latifah; Dede Ridwan; Lidya Nur Illahi; Risna Nurul Insani (Jurnal El-Audi, 2025)
Emotional development is a fundamental aspect of early childhood that significantly influences children's success in their daily lives and future learning. During early childhood, appropriate stimulation is essential to foster self-confidence, empathy, cooperation, and self-control. One effective approach to promoting these emotional competencies is through enjoyable, meaningful, and child-centered activities, such as creative gymnastics. This study aims to examine the effect of the "Guruku Tersayang" creative gymnastics program on the emotional development of early childhood at TK Negeri Pembina Cibeureum. The study was conducted because several children at the kindergarten had not yet achieved the expected level of emotional development. This research employed a descriptive qualitative method to systematically organize and interpret the data collected in the form of descriptive narratives. The participants consisted of all 34 children in Group A. Data were collected through observations and interviews focusing on children's emotional responses during the implementation of the "Guruku Tersayang" creative gymnastics activity. The findings indicate that the children's emotional development showed positive improvement and generally met the expected developmental indicators during their participation in the creative gymnastic activities. The program helped enhance children's self-confidence, cooperation, emotional expression, and positive interactions with their peers and teachers, suggesting that creative gymnastics can serve as an effective strategy for supporting emotional development in early childhood.